Efficiency optimization of direct torque control for permanent magnet synchronous motor - SUN Wen; ZHANG Xinghua (Gong-kuang zidonghua, 2014)
For problem of efficiency and power factor falling of permanent magnet synchronous motor running in light load and high speed, an efficiency optimization strategy of direct torque control for permanent magnet synchronous motor was proposed. The mathematical model was established based on considering iron loss of permanent magnet synchronous motor and analyzing relationships among power loss and torque, speed and stator flux linkage, and the optimal stator flux amplitude was derived. The optimal stator flux calculation module was embedded into direct torque control system, and speed-regulation control system of optimal efficiency of direct torque control for permanent magnet synchronous motor was constituted. The simulation results show that the strategy can effectively reduce the power loss of permanent magnet synchronous motor and improve operation efficiency of the motor.